ASSOCIAÇÃO ENTRE ANFOTERICINA B E Camellia sinensis: ATIVIDADE ANTIFÚNGICA E CITOTOXICIDADE - Oliveira, Viviane Matoso de (2012)
Amphotericin B, despite the advances in the research of new antifungal, still remains as antifungal of choice in the treatment for most systemic fungal infections due to the potency and wide spectrum of action. However, its use is limited due to its considerable toxicity, which leads to important side effects. Several studies have showed a range of natural compounds acting in association with amphotericin B, improving its activity in vitro and, consequently, reducing its dose. The aim of this study was to demonstrate the effect of white and black tea obtained from the plant Camellia sinensis in relation to two in vitro effects caused by amphotericin B: antifungal activity due to different strains of Candida sp and citotoxity in erythrocytes, polymorphonuclear leukocytes and Vero cells. Tests for antifungal activity with black and white tea, alone and in combination with amphotericin B were performed by broth microdilution according to the recommendations of the Clinical and Laboratory Standards Institute, which used three strains of American Type Culture Collection Strains and eight clinical isolates. The cytotoxicity experiment was performed trough stropophometric reading on erythrocyte absorbance released by the hemolysis induced by amphotericin B in the absence and presence of different concentrations of black and white tea. The cytotoxicity of polymorphonuclear leukocytes was assessed by cell viability test obtained by excluding trypan blue dye. The cell viability of Vero cells was determined by reducing the bromide 3 - [4,5-dimethylthiazol-2-yl] -2,5-difeniltetrazolium (MTT). The results showed that both white tea and black tea showed antifungal activity. From a total of eleven strains tested, the effect of the combination of white tea and black tea with amphotericin B, according to the Fractional Inhibitory Concentration Index (FICI) was additive for two strains with black tea and four strains with white tea. Concerning cytotoxicity on erythrocytes, both black tea and white tea inhibited hemolysis induced by amphotericin B. The association with black tea or white tea did not alter the amphotericin induced cytotoxicity in Vero cells and polymorphonuclear leukocytes. In the present study, it was demonstrated that white tea and black tea have additive antifungal activity when combined with amphotericin B against some strains of Candida sp. in addition to the protective effect of the toxicity of amphotericin B in erythrocytes. These results suggest that white and black teas deserve more detailed studies regarding the future potential use in combination with amphotericin B for antifungal improve their effectiveness and / or reduce your dose to reduce adverse effects.